Disruption of LEAF LESION MIMIC 4 affects ABA synthesis and ROS accumulation in rice - Hao Wu; Gaoxing Dai; Rao Yuchun; Kaixiong Wu; Junge Wang; Peng Hu; Yi Wen; Yueying Wang; Lixin Zhu; Bingze Chai; Jialong Liu; Guofu Deng; et al. (Crop Journal, 2023)
Lesion mimic mutants (LMMs) are advantageous materials for studying programmed cell death (PCD). Although some rice LMM genes have been cloned, the diversity of functions of these genes indicates that the mechanism of cell death regulation in LMMs needs further study. In this study, we identified a rice light-dependent leaf lesion mimic mutant 4 (llm4) that showed abnormal chloroplast structure, photoinhibition, reduced photosynthetic protein levels, massive accumulation of reactive oxygen species (ROS), and PCD. Map-based cloning and complementation testing revealed that LLM4 encodes zeaxanthin epoxidase (ZEP), an enzyme involved in the xanthophyll cycle, which functions in plant photoprotection, ROS scavenging, and carotenoid and abscisic acid (ABA) biosynthesis. The ABA content was decreased, and the contents of 24 carotenoids differed between the llm4 mutant and the wild type (WT). The llm4 mutant showed reduced dormancy and greater sensitive to ABA than the WT. We concluded that the mutation of LLM4 resulted in the failure of xanthophyll cycle, in turn causing ROS accumulation. The excessive ROS accumulation damaged chloroplast structure and induced PCD, leading eventually to the formation of lesion mimics.